An Analysis of Regional Financial Dependency, Local Rev-enue Effectiveness, and Fiscal Decentralization on Human Development in Madura Island - Pandu Fajar Pramudya; Marseto Marseto (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
This study investigates the relationship between fiscal dependence, the effectiveness of locally generated revenue (PAD), and the degree of fiscal decentralization on the Human Development Index (HDI) in four regencies on Madura Island Bangkalan, Sampang, Pamekasan, and Sumenep which have consistently reported the lowest HDI scores in East Java Province. Utilizing panel data from 2011 to 2023, the findings indicate that all regencies remain highly fiscally dependent, with fiscal dependency ratios exceeding 89%. Central government transfers dominate local budget structures, significantly limiting local fiscal autonomy. While PAD effectiveness shows notable achievements such as Pamekasan’s 136.09% realization rate its contribution to total regional revenue remains relatively low. This is reflected in the modest degree of fiscal decentralization, which ranges between 8.56% and 10.72%. Such fiscal limitations hinder the ability of local governments to invest in strategic sectors that directly impact human development, including education, healthcare, and public services. The analysis also reveals that despite effective PAD realization, its nominal value is insufficient to drive substantial improvements in HDI, especially when not supported by strengthened fiscal capacity and local economic mobilization. These findings suggest that PAD effectiveness alone does not translate into better human development outcomes without broader fiscal empowerment. Therefore, a comprehensive fiscal decentralization strategy is required one that not only enhances revenue generation but also improves budgetary governance and optimizes local economic resources. Strengthening local fiscal autonomy is essential for ensuring targeted, efficient, and equitable investment in human development sectors, ultimately fostering sustainable regional development across Madura Island.